Ultra-High Pressure Dynamic Compression of Geological Materials - Duffy, Thomas S.; Smith, Raymond F. (Frontiers in Earth Science, 2019)
Dynamic compression experiments on geological materials are important for understanding the composition and physical state of the deep interior of the Earth and other planets. These experiments also provide insights into impact processes relevant to planetary formation and evolution. Recently, new techniques for dynamic compression using high-powered lasers and pulsed-power systems have been developed. These methods allow for compression on timescales ranging from nanoseconds to microseconds and can often achieve substantially higher pressures than earlier gas-gun-based loading techniques. The capability to produce shockless (ramp) compression provides access to new regimes of pressure-temperature space while new diagnostics allow for a more detailed understanding of the structure and physical properties of materials under dynamic loading. This review summarizes these recent advances, focusing on results for geological materials at ultra-high pressures above 200 GPa.